Hukum Agraria Atas Keberadaan Bangunan Pada Ruang Atas Tanah - Musa Anthony Siregar; Zulkamaein Koto (Jurnal Nuansa Kenotariatan, 2015)
This research aim to examined how the legal protection of the existence of structures built in space on the top land from  perspective of Agrarian Law. And how the legal consequences of structures built in space on the top land by build operate transfer system. The discussion and analysis using the theory of law protection supported  by theory of the rule of law and the principles of land law. The research method is normative legal research to obtain the necessary data in connection with the period issues the data secondary data is consisting of primary legal materials.Second- ary legal materials, tertiary legal materials. Data analysis be done with juridical analysis of qualitative Research object is Senen Multipurpose Bridge that was built in space on the top land not on the land where that right is.That  was located between the two buildings and large shopping centre Pasar Senen and Plaza Atrium. Legal protection for the building space on the ground has not been found on the Agrarian  Law. Legal consequences of build operate transfer (BOT) system for the parties oc- cured namely the Provincial Goverment  DKI Jakarta and PT Jaya Real Property Tbk.Keywords: BOT system, space land, agrarian law